Onset of Addison Disease appeared during the first trimester of a twin pregnancy: A case report. Issue 5 (5th May 2021) - Tagetti, Angela; Marcon, Denise; Moghetti, Paolo; Spiazzi, Giovanna; Fava, Cristiano; Minuz, Pietro
Key Clinical Message: Addison Disease is an uncommon, life‐threatening condition affecting people at any age, including women during pregnancy. If left untreated, the disease can be rapidly fatal, but the prognosis is good if promptly recognized and hormones are replaced. Abstract : Addison Disease is an uncommon, life‐threatening condition affecting people at any age, including women during pregnancy. If left untreated, the disease can be rapidly fatal, but the prognosis is good if promptly recognized and hormones are replaced.